Plant Diversity Status in the Alpine Pasture of Shikari Devi, District Mandi, Himachal Pradesh: PLANT DIVERSITY IN ALPINE PASTURES - KUMAR, AKSHAY (Annals of Arid Zone, 2024)
Assessment of seasonal variation in the plant diversity of Shikari Devi alpine pasture provide basis for devising suitable strategies for management and conservation of the plant resources. The present study was conducted to understand the plant diversity of Shikari Devi alpine pasture, District Mandi, Himachal Pradesh during the year 2017 between 3100-3350 m elevation ranges. The study was carried out on seasonal basis. The study was carried out in summer season in May and winter season in November. A total of 62 plant species belonging to 30 families and 47 genera were recorded in summer season and a total of 18 plant species belonging to 9 families and 16 genera were recorded in winter season from the study area. Dominant families were Rosaceae, Asteraceae, Polygonaceae, Boraginaceae, Lamiaceae and Poaceae. Out of the 62 plant species recorded from the study area, 52 were medicinal plant species and four species viz., Bergenia stracheyi, Fritillaria roylei, Polygonatum verticillatum and Roscoea alpina were fall in the category of threatened plants.